(untitled) (Journal of Science Foundation, 2013)
The aim of this case report was to present a typical case of tuberous sclerosis. On 28 April 2012 a 8 year old female student reported as out patient of Ophthalmology Department, BSMMU, Dhaka. After taking history from the patient, ocular and systemic examinations were done. This patient had recurrent attacks of convulsion since 2 months of age and blurring of vision for 3 months. Ocular examination revealed fundus astrocytomas and patchy iris hypo-pigmentation. Systemic examination present with adenoma sebaceum. For diagnosis purpose, she was advised for investigation. CT scan of brain-Multiple cerebral calcification with bilateral multifocal cerebral atrophy. USG of whole abdomen-suggestive of cystitis. Methodical ocular and systemic examinations with appropriate investigations are mandatory to diagnose a case of tuberous sclerosis. DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14648 J. Sci. Foundation, 9(1&2): 59-63, June-December 2011